Kombinasi Proses Oxic dan Anoxic Menggunakan Metode Moving Bed Biofil Reactor dalam Meremoval Parameter Pencemar Pada Limbah Tahu - Hani Ghaisani; Yayok Suryo Purnomo (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Threats to the environment can come from various sources, including liquid waste from tofu production. This is due to the presence of pollutants in concentrations that exceed quality standards, which are discharged directly into water bodies from industrial wastewater without prior treatment. Therefore, a simple treatment method is needed to process liquid waste from the tofu industry to ensure that the quality meets established standards before disposal in order to prevent environmental contamination.Currently, the Moving Bed Biofilm Reactor (MBBR) method is becoming increasingly popular for wastewater treatment in both domestic and industrial applications. This method offers several advantages, including low energy consumption, no need for additional chemicals during operation, which avoids the generation of additional waste, and relatively simple operation and maintenance. In addition, MBBR does not require a large land area. Research shows that MBBR is effective in reducing concentrations of nitrogen compounds and organic compounds in wastewater. The highest removal efficiencies achieved are 92% for COD, 92% for TSS and 94% for NH3-N.